Analytical cryptanalysis upon N = p2q utilizing Jochemsz-May strategy. - Nurul Nur Hanisah Adenan; Muhammad Rezal Kamel Ariffin; Faridah Yunos; Siti Hasana Sapar; Muhammad Asyraf Asbullah (PLoS ONE)
This paper presents a cryptanalytic approach on the variants of the RSA which utilizes the modulus N = p2q where p and q are balanced large primes. Suppose [Formula: see text] satisfying gcd(e, ϕ(N)) = 1 where ϕ(N) = p(p - 1)(q - 1) and d < Nδ be its multiplicative inverse. From ed - kϕ(N) = 1, by utilizing the extended strategy of Jochemsz and May, our attack works when the primes share a known amount of Least Significant Bits(LSBs). This is achievable since we obtain the small roots of our specially constructed integer polynomial which leads to the factorization of N. More specifically we show that N can be factored when the bound [Formula: see text]. Our attack enhances the bound of some former attacks upon N = p2q.